Sub-synchronous oscillation damping of series-compensated DFIG wind farm using TID controller - Mahmoud A. El-Dabah; Mohamed H. Abdo; Mohamed Abdeen; Salah Kamel (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
Elevated levels of series compensation in transmission lines, especially those associated with wind farms, increase the likelihood of sub-synchronous oscillation (SSO) phenomenon, which poses a significant threat to the stability of the system. Inserting a supplementary damping controller (SDC) into a doubly-fed induction generator (DFIG) controller is one of the best-used methods for enhancing the system stability and damping the SSO. In this paper, the tilt-integral-derivative (TID) controller's ability to dampen the SSO and improve the system's stability will be investigated. The Gorilla Troops Optimizer (GTO) is utilized to determine the optimum values of the TID controller that achieve faster convergence. The controller, TID, is added to the rotor-side converter (RSC) inner current loops of DFIG. The effectiveness and capability of the developed method for mitigating the SSO have been tested by both the time-domain simulation and small-signal analysis at different SSO types (variable wind speeds, different compensation levels, and sub-synchronous control interaction). Compared to the traditional method (lead-lag compensators), the obtained results verify that the least SSO damping time and faster convergence have been achieved by the TID controller under all studied cases.